The role of language in the construction of Chinese ethnicity in Malaysia, Singapore, and China - Wong, Kevin Zi Hao (2016)
Existing studies find that Chinese Malaysians, Chinese Singaporeans, and Mainland Chinese are presently undergoing changes in their language use and language attitudes. However, these findings are often inconclusive, or leave unanswered questions about what these changes mean for the construction of Chinese ethnicity. This paper describes a questionnaire study investigating the role played by Mandarin, “Dialects”, and English in the everyday lives of 300 Chinese Malaysians, Chinese Singaporeans, and Mainland Chinese, in order to ascertain the relationship between these languages and the construction of Chinese ethnicity in Malaysia, Singapore, and Mainland China. Chinese Malaysians and Chinese Singaporeans are found to differ in ways that suggest the susceptibility of Chinese ethnicity to ideological construction by the state through language planning and policy. Meanwhile, Chinese Malaysians and Chinese Singapore differ from Mainland Chinese in a way that underscores the heterogeneity of Chinese ethnicity globally.